1988
DOI: 10.1002/ajh.2830270407
|View full text |Cite
|
Sign up to set email alerts
|

Red cell vacuoles: Their size and distribution under normal conditions and after splenectomy

Abstract: The frequency of occurrence of vacuoles in red blood cells was studied by transmission electron microscopy. Small vacuoles were found in about 13% of the cell sections, and they had a mean diameter of 130 +/- 72 nm (mean +/- SD). It can be estimated that there were about 20 small vacuoles per erythrocyte. The frequency of vacuoles was similar in density-separated cell fractions. In splenectomized patients, the small vacuoles were 4 times more frequent; there was again no difference in vacuole density between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
3
24
1
1
Order By: Relevance
“…The worsened IVH could be due to a not-as-efficient function of non-splenic mononuclear phagocytes in the ridding of defective or aged RBCs, in keeping with a previous report of RBCs with more vacuoles, particularly large ones, after splenectomy [28]. …”
Section: Discussionsupporting
confidence: 55%
“…The worsened IVH could be due to a not-as-efficient function of non-splenic mononuclear phagocytes in the ridding of defective or aged RBCs, in keeping with a previous report of RBCs with more vacuoles, particularly large ones, after splenectomy [28]. …”
Section: Discussionsupporting
confidence: 55%
“…The erythrocytederived vesicles isolated from the plasma of freshly drawn blood contained all haemoglobin components in a pattern similar to that of old erythrocytes, in accordance with the increased haemoglobin loss in the second half of the erythrocyte lifespan (Willekens et al, 2003). Vesicles were also observed in erythrocytes of all ages and were shown to accumulate after splenectomy (Reinhart & Chien, 1988). In asplenia, vesicles or vacuoles that are larger than 300 nm can be observed as 'pits' in the smear.…”
mentioning
confidence: 65%
“…6 In asplenia, not only a 4-fold increase in the number of these small vesicles can be found, but also abnormally big vacuoles (diameter Ͼ 300 nm) in about 30% of RBCs, some of which are known to contain hemoglobin. 6 A previous study indicated a positive relationship between the number of RBCs with big vacuoles ("pitted" cells, as seen with phase-contrast microscopy) and the HbA 1 percentage in RBC populations fractionated according to density. 7 Also, in this study the HbA 1 percentage of whole blood was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these vacuoles are known to contain hemoglobin. 6 A previous study indicated a positive relation between the number of RBCs with big vacuoles ("pitted" cells), and the HbA 1 percentage in RBC populations fractionated according to density. 7 Likewise, the HbA 1 percentage in whole blood was higher in asplenic individuals.…”
Section: Introductionmentioning
confidence: 96%